Peran Guru Bimbingan dan Konseling dalam Mencegah Bullying pada Siswa Berkebutuhan Khsusus di SMP Negeri 39 Semarang - widiana indra kusuma; Dini Rakhmawati; Padmi Dhyah Yulianti (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
This study aims to explore the role of Guidance and Counseling teachers in preventing bullying behavior toward students with special needs at SMP Negeri 39 Semarang. The study is motivated by the increasing number of bullying cases in schools, especially those involving students with special needs who are vulnerable to discrimination. This research employed a qualitative case study approach, with data collected through in-depth interviews, observation, and documentation. Data were analyzed using NVivo 12 software. The results reveal six key roles performed by guidance counselors: director, evaluator, facilitator, initiator, mediator, and motivator. These roles actively contribute to building an inclusive and safe school environment. The findings emphasize the significance of the counselor's role in preventive and intervention strategies against bullying in inclusive education settings.